ОРГАНІЗАЦІЙНО-АДМІНІСТРАТИВНЕ ЗАБЕЗПЕЧЕННЯ ПУБЛІЧНОЇ БЕЗПЕКИ І ПОРЯДКУ В ХАРКІВСЬКІЙ ОБЛАСТІ - РАЙНІН, Ігор Львович (SUPREMANCE OF LAW, 2016)
The article analyzes the regional program to ensure public safety and order in the Kharkiv region, certain issues addressed by the program, highlights program goals and objectives, described tasks and activities, to be performed in order to achieve a certain goal and generated the expected results from the implementation of the Programme, provided for the coordination and monitoring of its implementation, emphasized that the program is aimed at ensuring public safety and order, protection of human rights and freedoms, as well as the interests of society and the state, and fighting crime.